Assessment of HCM 2010 and HBS 2002 for Pedestrian Lane Quality In Indonesia (Case Study: Sardjito Hospital and Sudirman Office, Yogyakarta) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transportation was derived demand from primary activities from resident. Transport mobility is used transport modes, including for pedestrian as one of transport modes in the city. Pedestrians mobility are often forgotten on the transport infrastructure, like road. Connectivity between transportation nodes for first and last mile is crucial in encouraging the movement of people by walks. Indonesia still not have special procedures to assess pedestrian lane quality. Performance of road activity is often considered the same as motorized vehicles, like in Manual Kapasitas Jalan Indonesia 1997. On the otherhand, several regulations have been issued for the quality of pedestrian lanes, including HCM 2010 in America and the 2002 HBS in Germany. The purpose of this study was to determine the quality of pedestrian lanes using HCM 2010 and HBS 2002 in Indonesia. Research would be located in Sardjito Hospital and Jalan Sudirman Office, Yogyakarta. The results showed that lane width is one of the main components in assessing pedestrian quality from lane characteristic. HCM 2010 is focused onboth lane characteristic and pedestrian characteristic on pedestrian location to asses them. On the other side, HBS 2002 just focused on pedestrian characteristic as primary key to asses pedestrian lsnes quality The quality of the pedestrian paths for the Sardjito Hospital study is in class C for HCM 2010, but HBS 2002 scored for A class.On the other hand, Sudirman office area has scored A for both HCM 2010 and HBS 2002 assessment. The process and results of the assessment are expected to be a guideline used to develop manuals for the quality of pedestrian services in Indonesia